Taxonomic review of the chironomid genus Cricotopus v.d. Wulp (Diptera: Chironomidae) from Australia: keys to males, females, pupae and larvae, description of ten new species and comments on Paratrichocladius Santos Abreu - Drayson, Nick; Cranston, Peter S.; Krosch, Matt N. (Zootaxa, 2015)
The Australian species of the Orthocladiinae genus Cricotopus Wulp (Diptera: Chironomidae) are revised for larval, pupal, adult male and female life stages. Eleven species, ten of which are new, are recognised and keyed, namely Cricotopus acornis Drayson & Cranston sp. nov., Cricotopus albitarsis Hergstrom sp. nov., Cricotopus annuliventris (Skuse), Cricotopus brevicornis Drayson & Cranston sp. nov., Cricotopus conicornis Drayson & Cranston sp. nov., Cricotopus hillmani Drayson & Cranston, sp. nov., Cricotopus howensis Cranston sp. nov., Cricotopus parbicinctus Hergstrom sp. nov., Cricotopus tasmania Drayson & Cranston sp. nov., Cricotopus varicornis Drayson & Cranston sp. nov. and Cricotopus wangi Cranston & Krosch sp. nov. Using data from this study, we consider the wider utility of morphological and molecular diagnostic tools in untangling species diversity in the Chironomidae. Morphological support for distinguishing Cricotopus from Paratrichocladius Santo-Abreu in larval and pupal stages appears lacking for Australian taxa and brief notes are provided concerning this matter.